Trends in consumption of fats and oils among Indian tribal population over a period of 30 years: Findings of National Nutrition Monitoring Bureau surveys - Laxmaiah, A; Balakrishna, N; Arlappa, N; Meshram, II; Harikumar, R; Rao, K Mallikharjuna (Indian Journal of Community Health, 2014)
Introduction: In several randomized control trials, it was observed that the dietary fat content has a little, but a significant effect on energy consumption and body weight. The purpose of this communication was to assess fat consumption among tribals, time trends and its association with obesity and hypertension. Methods: These were community based cross-sectional studies, adopted multistage random sampling procedure. The subjects were covered from 120 randomly selected villages each from 9 states in India. Information on household socio-economic & demographic and food intakes were collected. Anthropometric parameters and blood pressure were measured by using standard equipment and procedures. Results: The mean intake of food and nutrients were assessed in 14,324, 32,023, and 41507 tribal subjects in 1985-87, 1998-99 and 2008-09, respectively. The mean consumption of visible fats was 10g/CU/day, as against requirement of 20g and increased from 7g in 1985-87 to 10g in 2008-09. The percentage of energy obtained from total fat (20.8g/day) was 10% as against safe limit of 20%. The consumption of total dietary fats was increased significantly over a period of 3 decades in all the age groups, but it is less than recommended levels of ICMR. The fat intake was significantly associated with obesity and hypertension. Conclusions: Even though fat consumption was increased in all the age groups, but less than the recommended levels of ICMR. The consumption of fat was significantly associated with obesity and hypertension. There is an urgent need to create awareness among tribal population to consume adequate and quality of fats.